INTANGIBLE ASSETS IN BUDGET ORGANIZATIONS AND THEIR EVALUATION (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Intangible assets in budget organizations and the issues of their evaluation are highlighted in this scientific research work. The calculation model for the accounting unit, object and cost of intangible assets in budget organizations is explained. The revaluation model of intangible assets is also scientifically based.